Bereavement outcomes in family members of those who died in acute care hospitals before and during the first wave of COVID-19: A cohort study. (September 2022) - Downar, James; Parsons, Henrique A.; Cohen, Leila; Besserer, Ella; Adeli, Samantha; Gratton, Valérie; Murphy, Rebekah; Warmels, Grace; Bruni, Adrianna; Bhimji, Khadija; Dyason, Claire; Enright, Paula; et al.
Background: The COVID-19 pandemic has caused millions of deaths worldwide, leading to symptoms of grief among the bereaved. Neither the burden of severe grief nor its predictors are fully known within the context of the pandemic. Aim: To determine the prevalence and predictors of severe grief in family members who were bereaved early in the COVID-19 pandemic. Design: Prospective, matched cohort study. Setting/Participants: Family members of people who died in an acute hospital in Ottawa, Canada between November 1, 2019 and August 31, 2020. We matched relatives of patients who died of COVID (COVID +ve) with those who died of non-COVID illness either during wave 1 of the pandemic (COVID −ve) or immediately prior to its onset (pre-COVID). We abstracted decedents' medical records, contacted family members >6 months post loss, and assessed grief symptoms using the Inventory of Complicated Grief-revised. Results: We abstracted data for 425 decedents (85 COVID +ve, 170 COVID −ve, and 170 pre-COVID), and 110 of 165 contacted family members (67%) consented to participate. Pre-COVID family members were physically present more in the last 48 h of life; the COVID +ve cohort were more present virtually. Overall, 35 family members (28.9%) had severe grief symptoms, and the prevalence was similar among the cohorts ( p = 0.91). Grief severity was not correlated with demographic factors, physical presence in the final 48 h of life, intubation, or relationship with the deceased. Conclusion: Severe grief is common among family members bereaved during the COVID-19 pandemic, regardless of the cause or circumstances of death, and even if their loss took place before the onset of the pandemic. This suggests that aspects of the pandemic itself contribute to severe grief, and factors that normally mitigate grief may not be as effective.